The Effect of a Pre-Trial Range Demonstration on Subjective Evaluations Using Category Rating of Discomfort Due to Glare. Issue 1 (2nd January 2021) - Kent, Michael G; Fotios, Steve
ABSTRACT: Category rating is a procedure commonly used to evaluate visual discomfort due to glare. One recommended step for good practise in a category rating procedure is to use a pre-trial demonstration (PTD) of the range of stimuli to be experienced. However, PTD have rarely, if at all, been used in past research on discomfort glare. In this study, two experiments were conducted to test the influence of the PTD on evaluations of discomfort due to glare. In the first experiment participants evaluated four glare source luminances with, and without, a PTD. The results suggest that using a PTD increased the reported degree of discomfort perceived for the same glare setting, although this may depend on the manner in which the PTD is presented. In the second experiment, participants evaluated four glare source luminances using PTD with three different luminance ranges: the results suggest this had significant effect on discomfort evaluations in that evaluations of discomfort were lower when a higher luminance range was used. Along with other recent studies, these findings suggest a need to derive a more robust procedure for measuring the discomfort due to glare.